Pinensins: The First Antifungal Lantibiotics. Issue 38 (24th July 2015) - Mohr, Kathrin I.; Volz, Carsten; Jansen, Rolf; Wray, Victor; Hoffmann, Judith; Bernecker, Steffen; Wink, Joachim; Gerth, Klaus; Stadler, Marc; Müller, Rolf
Abstract Lantibiotics (lanthionine‐containing antibiotics) from Gram‐positive bacteria typically exhibit activity against Gram‐positive bacteria. The activity and structure of pinensin A (1) and B (2), lantibiotics isolated from a native Gram‐negative producer Chitinophaga pinensis are described. Surprisingly, the pinensins were found to be highly active against many filamentous fungi and yeasts but show only weak antibacterial activity. To the best of our knowledge, lantibiotic fungicides have not been described before. An in‐depth bioinformatic analysis of the biosynthetic gene cluster established the ribosomal origin of these compounds and identified candidate genes encoding all of the enzymes required for post‐translational modification. Additional encoded functions enabled us to build up a hypothesis for the biosynthesis, export, sensing, and import of this intriguing lantibiotic.